The Relationship between the Support Factor from SME Actors and the Officer Support regarding the Acceptance of the Importance of Distribution Permits for Pempek SMEs in Palembang City - Yarnis Yarnis; Misnaniarti Misnaniarti; Yuanita Windusari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
There are still many food products that do not have a P-IRT or a food production permit for household industries. This is influenced by the lack of knowledge of the procedure for obtaining a P-IRT certificate by industry players. The purpose of this study was to analyze the relationship between knowledge and acceptance of the importance of distribution permits for Pempek SMEs in Palembang City. This research method uses descriptive-analytic through cross-sectional design. The population in this study is Pempek SMEs. The sampling technique is a total sampling of 30 business actors. The results of the study showed that as many as (60.0%) received distribution permits from business actors, and the results of the analysis showed that there was a relationship between business actors' support and the acceptance of the importance of distribution permits for Pempek SMEs in Palembang City (p = 0.021 < 0.05, OR = 10,000). Based on the results above, it is concluded that business actors do not support the importance of distribution permits for pempek business actors in Palembang City, so it is suggested that all business actors raise more awareness regarding the issuance process of distribution permits so that their businesses can develop and the goods marketed and consumed by consumers are guaranteed cleanliness and health and do not interfere with public health.